Beauty and The Beast . . - Caroline Wasson Thomason
Exquisite illustrations of Beauty and her mysterious suitor, the Beast, are set in a magical castle where animals dressed in period costumes serve them. Woven into glorious tapestries throughout are hidden clues hinting at the Beast's secrets, setting Brett's version apart from others.